Human Brain/Cloud Interface - Martins, Nuno R. B.; Angelica, Amara; Chakravarthy, Krishnan; Svidinenko, Yuriy; Boehm, Frank J.; Opris, Ioan; Lebedev, Mikhail A.; Swan, Melanie; Garan, Steven A.; Rosenfeld, Jeffrey V.; Hogg, Tad; Freitas, Robert A. (Frontiers in Neuroscience, 2019)
The internet comprises a decentralized global system that serves humanity’s collective effort to generate, process, and store information. A significant portion of this data is currently processed and stored in the cloud, and the last few years have witnessed the doubling of cloud storage and cloud computing. Given such tremendous growth there is an urgent need to create a stable, secure, and continuous real-time system for interfacing the human brain with the cloud. One promising strategy for the creation of human brain/cloud interface (B/CI) technologies may be referred to as “neuralnanorobotics.” Neuralnanorobotic technology might well emerge from efforts to comprehensively address cognitive disorders and is expected to facilitate the accurate diagnoses and eventual cures for the ~400 conditions that affect the human brain. Neuralnanorobotics is also anticipated to have numerous non-medical applications -- for example, serving as a platform to enable a robust, ultrahigh-resolution interface between the human brain and the cloud. Neuralnanorobotics may permit a safe, secure, and stable real-time whole-human brain interface with the cloud, allowing for controlled connectivity between neural activity and external data storage and data processing. This strategy may involve direct and comprehensive monitoring of the estimated ~86 x 109 neurons of the human brain, along with its estimated ~2 x 1014 synapses, through the use of nanometric medical nanorobotics. Subsequent to navigating the human vasculature, three species of neuralnanorobots (endoneurobots, gliabots, and synaptobots) would traverse the blood-brain barrier, enter the brain parenchyma, ingress into individual human brain cells, and autoposition themselves at the axon initial segments of neurons (endoneurobots), within glial cells (gliabots), and in intimate proximity to every synapse or group of synapses (synaptobots). A neuralnanorobotically assisted human B/CI is expected to give rise to an extensive panoply of applications, among which would be the application of serving as a personalized conduit for individuals to obtain direct, instantaneous access to any facet of cumulative human knowledge available in the cloud. Other anticipated applications include a myriad of opportunities for improving education, intelligence, entertainment, traveling, and other interactive experiences.